Ecological Imaginations in Latin American Fiction - Barbas-Rhoden, Laura, 1974- (Book collections on Project MUSE., 2011)
By integrating the use of futuristic novels, Barbas-Rhoden pushes the ecocriticism discussion beyond the realm of 'nature writing'. She avoids the cliches of literary nature and reminds readers that today's urban centres are also part of Latin America and its environmental crisis.